Образ «другого» в новогреческой литературе - Нёрба, М.Н.; Александрова, О.Н. (Культура народов Причерноморья, 2014)
Работа посвящена актульному на сегодняшний день в философии и литературоведении
вопросу проблемы «другого» в новогреческой литературе на примере романа Мити Карагациса
«Югерман». В исследовании поднимается проблема национальной самоидентификации, анализируется
понятие «национальный характер»; исследуется термин «имагология»; рассматривается оппозиция
«свои-чужие» на примере романов М. Карагациса Робота присвячена актуальному на сьогоднішній день питанню про образ «іншого» в
новогрецькій літературі на прикладі твору Миті Карагаціса «Югерман». У дослідженні аналізується
авторська своєрідність трактування образу головного героя твору - офіцера Югермана - у творчості
грецького письменника. The article by Alexandrova O. N. and Norba M. N. «The Image of the «Other» in the New Greek
Literature » is devoted to the actual at present question about the image of the «other» in the new Greek
literature using as an example the literary work by Mitya Karagatsis «Yugerman». The actuality of the work is
in the fact that problems of the identity at the end of the ХХ century – beginning of the XXI century appeared to
be in the very center of the public attention what have caused the interest to it from literary critics’ side.
The main purpose of the article is to analyze the image of the «other» in the new Greek literature and in the
literary works by М. Karagatsis. Along with it the authors fulfill such tasks: to consider the notion «national
character»; to characterize the term «imagology»; to compare the opposition «our own people – alien ones».
In the research one analyzes the author’s originality of the expression of the main character’s image – military
officer Yugerman’s one – in the literary activities of the Greek writer.